The Existence of LGBT and the Role of the MUI in Responding to the LGBT Movement in South Sulawesi - Rahmawati Rahmawati; Budiman Budiman; Fatmawati Fatmawati; Mutiara Mutiara (LPPM IAIN Parepare, 2023)
This article is motivated by the issue of the transgender community, which will hold a transgender fashion show combined with the recitation of the Al-Qur’an in Sidrap, South Sulawesi. This activity was criticized by Ulema Council (MUI) in South Sulawesi because it was considered being injurious to Islamic religious values ​​and even insulting religion. However, this community still has space in society because of human rights considerations. The aim of this article is to analyze the role of ulama in responding to LGBT developments and movements in South Sulawesi. The research method used is qualitative research with a sociological, normative, juridical approach. The research results show that the existence of Lesbian Gay Bisexual Transgender (LGBT) is still widely rejected by society in South Sulawesi. The role of religious figures is quite influential in responding to the existence of transgender communities in religious communities. This is proven by the failure of several transgender campaign activities in South Sulawesi. Seeing this phenomenon, the government should be quick to respond to this by opening a space for dialogue for the transgender community and ulama, as well as providing counseling services for this community.